Evaluating the activity of dispensing opioid analgesic medication - Elena Dinte; Radu Borza; Oana Mocan Gurka (Amaltea Medical Publishing House, 2021)
Mannitol is used in freeze-dried products as a bulking agent, consistency enhancer, or stabilizer, having the lowest hygroscopicity among the excipients commonly used as consistency agents, therefore it can be used in the formulation of unstable preparations. Lyophilization is a complex method of drying a solution at low temperature and low-pressure that addresses especially thermolabile substances, such as proteins. The end-product is a lyophilized powder, which can be administered parenterally after reconstitution with suitable solvents. The objective of this study was to evaluate freeze-dried products obtained from mannitol solutions of different concentrations. Mannitol solutions of increasing concentrations of 2.5%, 5%, 7.5%, and 10% were prepared by dissolving mannitol in distilled water. The prepared solutions were freeze-dried after a preliminary DSC analysis, in which the thermal phenomena that occurred during lyophilization were identified. Freeze-dried preparations were analyzed by different methods: macroscopic analysis by visual assessment and comparison with data from the literature, texture analysis by which several properties of these preparations were studied (hardness, deformation, mechanical work, adhesive strength, fracture resistance, and the number of fractures), evaluation of reconstitution time and porosity. The mannitol used in the lyophilization process, being partially amorphous, required differential calorimetric analysis to establish its glass transition and to avoid the collapse of the preparations during lyophilization. Finally, NIR spectroscopy was used to predict the characteristics of the freeze-dried powders in a non-invasive manner, without prior sample preparation.